Turkish Music Reform and Russian Model: A Discussion from the Viewpoint of Comperative Music Sociology - Ayas, Onur Gunes (AHMET YESEVI UNIV, 2016)
It is widely accepted that Turkish music reform has been influenced by the Russian model. However, the Russian attempts of forming a modern national music within the Western musical tradition have represented a solution to the problems of Russian musicians, while the official attempts of forming a totally new Westernized national music in Turkey by excluding the Ottoman musical legacy have caused not only serious practical problems but also a deep identity crisis in itself. In this article, through analyzing both the making of the modern Russian music and the attempts of excluding the Ottoman musical legacy and resulting failure of Turkish music reform, I will try to show that there is not a great deal of similarity between the Russian and Turkish experiences of musical modernization. I will also argue that this dissimilarity stems from the different international-historical roles played by these two nations and the different specific characteristics of these two musical traditions as well.
Keywords: Sociology of music; Russian music; Ottoman Music; Turkish Music Reform Russian Five; Westernization; modernization; Area Studies